FEATURES OF PROCESSES OF DIFFERENTIATION GINGIVAL EPITHELIUM IN DYNAMIC MENSTRUAL CYCLE - Гасюк, Н.В.; Єрошенко, Г.А. (World of Medicine and Biology, 2015)
In the article the results of a comprehensive study of the process of cytological differentiation gingival epithelium younger women, the dynamics of the menstrual cycle. These data make it possible to assert the presence of cyclic relationship gingival epithelial differentiation process of the phase of the menstrual cycle. These are the stereotypical cellular composition tsytohram vagina and gingiva in the appropriate phase and quantitative changes in the late phase folikulinovu that reflect the highest level of estrogen saturation of the body.
Keywords: epithelium; cellular composition; nucleus; cytoplasm